Flexible silicon-free phase change high thermal conductive gasket and preparation method thereof
Patent Information
- Application Number
- CN202611183260.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]针对上次存在的问题或不足,为解决现有技术存在的硅污染、高温泄漏、导热率低、柔性差、工艺复杂等问题,本发明提供了一种柔性无硅相变高导热垫片及其制备方法,垫片兼具高导热、柔性、热稳定性优异,其制备方法采用加热搅拌混合-热压成型-压延定型的可工业化方法
[0025]综上所述,本发明采用粒度大致相当、但外部形貌不同的片状六方氮化硼微球与球状氧化铝作为复配导热填料,依靠等径球形颗粒规整密堆积特性,在SEBS-石蜡双相基体内部搭建均匀、稳定的填料基础网络骨架;同时利用氮化硼微球在复合加工过程中可部分原位解离细化的独特结构特点,解离生成的次级纳米颗粒精准填充球体堆积间隙,修补导热通路缺陷,在基体内部形成大球搭桥、小球补隙、多级贯穿的致密三维导热网络。得益于球形填料表面光滑、与SEBS弹性相、石蜡相变相均具备优异的界面相容性,该多级导热网络能够均匀浸润、连续铺展于双相基体体系中,实现导热通路在整个复合材料体系内全域、均匀、贯通分布。在此基础上,SEBS高分子弹性网络紧密包覆石蜡相变组分与整体导热填料体系,有效束缚熔融石蜡流动、杜绝高温渗漏问题,同时完整保留石蜡优异的潜热储热与恒温控温特性。
Smart Images

Figure CN122898149A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermal conductive materials technology, specifically relating to a flexible silicon-free phase change high thermal conductivity pad and its preparation method. It is suitable for scenarios such as heat dissipation of electronic devices and buffering and heat conduction of mechanical components, and is especially suitable for application scenarios with high requirements for the thermal conductivity of the pad. Background Technology
[0002] With the rapid development of electronic devices such as 5G communications, artificial intelligence, new energy vehicles, and high-performance servers towards high power, miniaturization, and high-density integration, the heat generation per unit area of devices is increasing dramatically. Thermal management has become a key factor restricting the stability, lifespan, and operating efficiency of equipment. Phase change thermal interface materials, with their advantages of high latent heat absorption during solid-liquid phase transitions, temperature self-adaptation, good interface wettability, and low contact thermal resistance, can quickly absorb the instantaneous high heat flux density of chips, stabilize the operating temperature of devices, and fill the microscopic gaps between heat sources and heat sinks. They have become one of the core materials for thermal management in mid-to-high-end electronic devices.
[0003] Currently, most commercially available phase change thermal interface materials are based on organosilicon systems, with components such as silicone oil, silicone rubber, and silica providing phase change support and structural stability. Although silicon-based systems have advantages such as good heat resistance, adjustable viscosity, and excellent formability, they suffer from serious problems of siloxane volatilization and migration contamination in practical applications. This can easily lead to contact failure, signal interference, and optical component contamination, making it difficult to meet the usage requirements of silicon-sensitive scenarios such as automotive electronics, servers, optical modules, and radio frequency devices.
[0004] To address the issue of silicon contamination, silicon-free phase change thermal interface materials have become a research hotspot in recent years. Silicon-free systems often employ polyolefins, styrene-based thermoplastic elastomers, and acrylates as the supporting framework, with paraffin wax and fatty acids as the phase change heat storage medium, combined with inorganic thermally conductive fillers to improve thermal conductivity. Currently, most commercially available thermal pads are made with a single polymer as the matrix, combined with thermally conductive fillers, but they have several shortcomings: some pads use rigid polymers as the matrix, resulting in poor flexibility, brittleness, and an inability to adapt to irregular gaps; others use flexible matrices, but the thermally conductive fillers have poor compatibility with the matrix and are unevenly dispersed, leading to poor thermal conductivity and difficulty in meeting the heat dissipation requirements of high-power equipment.
[0005] In summary, existing phase change thermal interface materials still cannot simultaneously meet the comprehensive requirements of being silicon-free and environmentally friendly, having a fixed shape to prevent leakage, high thermal conductivity, high flexibility, high insulation, and being mass-producible. Therefore, developing a novel silicon-free phase change thermal interface material with synergistic support from a thermoplastic elastomer and an organic framework, high thermal conductivity, and high latent heat storage, along with a simple, stable, and scalable preparation process, is of significant practical importance and application value for promoting the upgrading of thermal management technology for silicon-sensitive electronic devices. Summary of the Invention
[0006] In response to the problems or shortcomings of the previous invention, and to address issues such as silicon contamination, high-temperature leakage, low thermal conductivity, poor flexibility, and complex processes in existing technologies, this invention provides a flexible silicon-free phase change high thermal conductivity pad and its preparation method. The pad combines high thermal conductivity, flexibility, and excellent thermal stability. Its preparation method employs an industrially feasible approach of heating and stirring mixing, hot pressing molding, and calendering.
[0007] A flexible, silicone-free phase change high thermal conductivity pad comprises the following raw material components: thermoplastic elastomer, crosslinking agent, phase change material, first thermally conductive filler, and second thermally conductive filler. The raw material components, by mass percentage, are: thermoplastic elastomer 5–30 wt%, paraffin wax 5–35 wt%, first thermally conductive filler 30–75 wt%, second thermally conductive filler 5–30 wt%, and crosslinking agent 0.5–2 wt% of the total mass of thermoplastic elastomer and phase change material, with a total quantity of 1. The components are mixed thoroughly, hot-pressed, and then calendered for final shaping.
[0008] The thermoplastic elastomer serves as a continuous phase, providing flexibility, mechanical support, and processing performance for the entire composite material system.
[0009] The phase change material is used to undergo a solid-liquid phase change near the operating temperature of electronic devices to improve the material's wetting ability at the contact interface and reduce the interface contact thermal resistance.
[0010] The first and second thermally conductive fillers have different microstructures and together they form a thermally conductive network, improving the overall thermal conductivity of the composite material.
[0011] Furthermore, the thermoplastic elastomer is one or a combination of two or more of SEBS, OBC, SBS, POE, TPU, and TPEE.
[0012] Furthermore, the phase change material is paraffin wax with a melting point of 40–80°C, enabling the material to undergo a phase change within the normal operating temperature range of electronic devices, thereby improving the interface bonding performance.
[0013] Furthermore, the first thermally conductive filler is spherical alumina particles with a particle size of 10–50 μm; the second thermally conductive filler is plate-shaped hexagonal boron nitride with an average particle size of 10–50 μm, to improve the in-plane thermal conductivity of the material. The mass ratio of alumina to hexagonal boron nitride is 90:10 to 80:20.
[0014] Furthermore, the alumina is compounded with different particle sizes to improve the packing density of the filler.
[0015] Furthermore, the crosslinking agent is 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane (DCP).
[0016] The method for preparing the above-mentioned flexible silicon-free phase change high thermal conductivity pad is characterized by comprising the following steps:
[0017] Step 1, Material preparation: Weigh the thermoplastic elastomer, crosslinking agent, phase change material, first thermally conductive filler and second thermally conductive filler according to the set mass ratio.
[0018] Step 2: Prepare thermally conductive slurry: Add the raw materials prepared in Step 1 to a planetary vacuum mixer and mix them evenly to obtain a thermally conductive slurry, so that the phase change material is uniformly coated on the surface of the thermally conductive filler.
[0019] During the stirring process, the combined motion of revolution and rotation ensures that alumina and boron nitride are uniformly dispersed in the continuous phase of the thermoplastic elastomer, and that the phase change material is uniformly coated on the surface of the thermally conductive filler. Preferably, the stirring speed is 300–1500 rpm, and the stirring time is 10–60 min; mixing under vacuum conditions reduces air entrainment and improves the material density.
[0020] Step 3, hot pressing: Place the slurry obtained in step 2 into a preheated mold for hot pressing. The hot pressing temperature is 80-180℃, the hot pressing pressure is 2-20 MPa, and the holding time is 5-60 min.
[0021] During hot pressing, the thermoplastic elastomer gradually softens and flows. After cross-linking, the thermoplastic elastomer forms a continuous three-dimensional elastic network. The phase change material (such as paraffin wax) is uniformly distributed in the cross-linked network. Under pressure, the thermally conductive filler further closes and forms a preliminary thermally conductive pathway. Through hot pressing, the internal porosity of the material can be significantly reduced, and the density of the composite system can be improved. During use, the phase change material and the thermally conductive filler are constrained by the cross-linked network, which improves the dimensional stability and high-temperature anti-leakage performance of the material system.
[0022] Step 4: Calendering and shaping; The sheet material after hot pressing in step 3 is fed into a calendering machine for continuous calendering. The calendering temperature is 50-70℃ and the calendering ratio is 1.2-2.0, so that the sheet-like hexagonal boron nitride is oriented along the calendering direction. The calendering thickness is controlled at 0.2-5mm. After calendering, it is cooled (natural cooling or temperature-controlled cooling) to obtain a flexible silicon-free phase change high thermal conductivity pad.
[0023] During calendering, the material undergoes further plastic flow, and the internal fillers rearrange along the calendering direction under shear force, increasing the contact area between the thermally conductive fillers and further improving the thermal conductivity network. Simultaneously, by controlling the calendering gap, the resulting thermally conductive pad has a uniform thickness and a flat surface. Specifically, the platen hexagonal boron nitride aligns along the calendering direction during the calendering process, forming a continuous thermally conductive skeleton. Spherical alumina fills the spaces between the hexagonal boron nitride plates, reducing the interfacial thermal resistance in the thermal conductivity network. Furthermore, the continuity of the thermal conductivity network is further improved through the use of two thermally conductive fillers with different morphologies.
[0024] Furthermore, each raw material component is cleaned and dried before use to remove adsorbed moisture and avoid the generation of bubbles during processing.
[0025] In summary, this invention employs plate-shaped hexagonal boron nitride microspheres with roughly similar particle sizes but different external morphologies, along with spherical alumina, as composite thermally conductive fillers. Relying on the regular, dense packing characteristics of the uniform-diameter spherical particles, a uniform and stable filler network framework is constructed within the SEBS-paraffin biphase matrix. Simultaneously, utilizing the unique structural characteristic of boron nitride microspheres, which can partially dissociate and refine in situ during composite processing, the resulting secondary nanoparticles precisely fill the gaps between the spheres, repairing defects in the thermal conductivity pathways. This forms a dense, three-dimensional thermally conductive network within the matrix, characterized by large spheres bridging, small spheres filling gaps, and multi-level penetration. Thanks to the smooth surface of the spherical fillers and their excellent interfacial compatibility with both the SEBS elastic phase and the paraffin phase, this multi-level thermally conductive network can uniformly impregnate and continuously spread throughout the biphase matrix system, achieving a uniform, continuous, and universal distribution of thermal conductivity pathways throughout the entire composite material system. Based on this, the SEBS polymer elastic network tightly encapsulates the paraffin phase change components and the overall thermally conductive filler system, effectively restricting the flow of molten paraffin and eliminating high-temperature leakage problems, while fully preserving the excellent latent heat storage and constant temperature control characteristics of paraffin. Attached Figure Description
[0026] Figure 1 The image shows a physical picture of the silicone-free thermal pad prepared for Example 3.
[0027] Figure 2 X-ray diffraction pattern of the silicon-free thermal pad prepared for the example.
[0028] Figure 3 Thermal conductivity of the silicone-free thermal pad prepared for the example at different temperatures.
[0029] Figure 4 The thermal resistance of the silicone-free thermal pad prepared for the example at different temperatures.
[0030] Figure 5 The particle size classification of thermally conductive fillers is used as an example. Detailed Implementation
[0031] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments.
[0032] In this embodiment, thermoplastic elastomer SEBS is used as the organic framework material, paraffin is used as the auxiliary flexible phase and the mobile phase, and alumina and sheet-like hexagonal boron nitride are used as composite thermally conductive fillers. The cross-linking reaction of SEBS is initiated by bis(2,5-diphenyl)-p-ethyl (DCP) to construct a stable three-dimensional cross-linked network. At the same time, combined with hot pressing densification and calendering-induced orientation processes, a continuous and efficient thermally conductive network is formed while ensuring the flexibility of the material. Thus, a flexible thermally conductive pad with excellent thermal conductivity, compression resilience and thermal stability is prepared.
[0033] The SEBS used in the examples is a commercially available thermoplastic elastomer; the paraffin melting point is 42-58 °C; the alumina is spherical micron-sized alumina powder with an average particle size of 10-50 μm; the boron nitride is plate-shaped hexagonal boron nitride powder with an average particle size of 10-50 μm; and the crosslinking agent is bis(2,5-diphenyl)propionate (DCP).
[0034] Weigh each component according to the design ratio. First, place the paraffin wax in a stirring container and heat it to 70 ℃ to melt it completely; then add SEBS, heat the system to 130 ℃ and stir for 30 min to allow the SEBS to fully swell and form a uniform continuous phase.
[0035] Alumina and boron nitride were added to the above system in multiple portions according to a predetermined ratio, and the mixture was further kneaded at 130°C for 20 min to fully wet and uniformly disperse the thermally conductive filler. Then, bis(2,5)5 was added and the mixture was further kneaded for 15 min to uniformly disperse the crosslinking agent in the composite system.
[0036] After mixing, the slurry is transferred to a preheated mold and hot-pressed at 170°C and 10 MPa for 20 minutes to allow SEBS to crosslink and densify the material. After hot pressing, the pressure is maintained and cooled to below 50°C before demolding.
[0037] After demolding, the sheet material is calendered to a predetermined thickness to obtain a flexible thermally conductive pad. During the calendering process, the sheet-like hexagonal boron nitride undergoes a certain degree of orientation alignment, further improving the continuity of the thermally conductive network.
[0038] Example 1
[0039] In this embodiment, the mass fractions of SEBS and paraffin are maintained at 18 wt% and 22 wt%, respectively, and the total content of thermally conductive filler is 50 wt%, wherein the mass ratio of alumina to boron nitride is 80:20, that is, alumina is 40 wt% and boron nitride is 10 wt%; the amount of DCP added is 1 wt%.
[0040] During the preparation process, sheet-like BN begins to form bridging structures between alumina particles, while alumina fills the spaces between the BN sheets, thus constructing a preliminary multi-scale thermally conductive network. After hot pressing and calendering, the BN undergoes a certain degree of orientation along the calendering direction, which is beneficial for improving the continuity of the thermal conductivity pathway.
[0041] Example 2
[0042] In this embodiment, the mass fractions of SEBS and paraffin are 18 wt% and 22 wt%, respectively, and the total content of thermally conductive filler is 50 wt%. The mass ratio of alumina to boron nitride is adjusted to 60:40, that is, alumina is 30 wt% and boron nitride is 20 wt%. The amount of DCP added is kept at 1 wt%.
[0043] As the BN content increases, it becomes easier for the sheet-like BN to form a continuous overlapping structure, further enhancing the connectivity of the thermally conductive network. Alumina particles filling the spaces between the BN sheets effectively reduce the porosity between fillers, resulting in a denser, synergistic thermally conductive structure.
[0044] Example 3
[0045] In this embodiment, the mass fractions of SEBS and paraffin are 18 wt% and 22 wt%, respectively, the total content of thermally conductive filler is 50 wt%, and the mass ratio of alumina to boron nitride is 40:60, that is, alumina is 20 wt% and boron nitride is 30 wt%; the amount of DCP added is 1 wt%.
[0046] As the BN content increases further, the viscosity of the system increases significantly. Therefore, a slow, batch-feeding method is used during mixing to ensure uniform dispersion. After hot pressing, a more continuous, sheet-like thermally conductive framework is formed, and the BN orientation becomes more pronounced during calendering, which is beneficial for obtaining higher thermal conductivity.
[0047] Comparative Example 1
[0048] Compared with Example 1, this comparative example only removes boron nitride, while keeping the other components and process conditions the same.
[0049] The resulting material mainly relies on the contact between alumina particles to form a thermal conduction path. The continuity of the thermal conduction network is relatively weak, which can be used to compare the synergistic thermal conduction effect before and after the introduction of BN.
[0050] Comparative Example 2
[0051] In this comparative example, only boron nitride was used as the thermally conductive filler, and the total filler content was kept at 60 wt%. The remaining composition and process parameters were the same as in Example 1.
[0052] Because of the lack of alumina particles to fill the gaps between BN sheets, BN is prone to local stacking, and there may be many voids in the thermally conductive network. This can be used to verify the role of alumina in improving filler packing density and reducing interfacial thermal resistance.
[0053] The final thermal pad samples prepared for each of the above embodiments and comparative examples were tested and characterized: Figure 1 A photograph of the silicon-free thermal pad prepared in Example 3; Figure 2 The X-ray diffraction pattern of the silicon-free thermal pad prepared for the example shows that the characteristic diffraction peaks corresponding to aluminum oxide and boron nitride appear in the XRD pattern of the prepared silicon-free thermal pad, indicating that the thermally conductive filler maintains its original crystal structure during the composite process. Figure 3 Thermal conductivity of the silicone-free thermal pads prepared for the examples and comparative examples at different temperatures; Figure 4 The thermal resistance of the silicone-free thermal pads prepared for the examples was measured at different temperatures. The test results showed that as the test temperature increased, the thermal conductivity of the composite thermal pads gradually increased, while the contact thermal resistance continuously decreased. Because the sheet-like hexagonal boron nitride provides an efficient heat transfer path, and the alumina particles reinforce the connection of the thermally conductive nodes to form a stable multi-scale synergistic thermal conductive network, the composite system of Example 3 exhibited the best temperature response performance. Figure 5 As an example, the particle size classification of thermally conductive fillers was used. The test results showed that the plate-like hexagonal boron nitride microspheres and the spherical alumina had similar particle size distributions, indicating that the two fillers had good matching in spatial scale and reduced the problem of uneven filling caused by size differences.
[0054] As can be seen from the above embodiments, this invention constructs a silicon-free phase change thermal interface material based on SEBS through a novel material system design and preparation method. This material exhibits the following advantages in terms of thermal conductivity, material flexibility, interface compatibility, and environmental friendliness:
[0055] Using SEBS as the silicone-free organic framework material, the produced silicone-free thermal pads do not generate silicides (VOCs) under high-temperature operating environments, avoiding potential contamination from volatile VOCs deposited on the surface of electronic devices. The material of this invention exhibits long-term stability and is particularly suitable for camera modules, high-precision sensors, and industrial applications requiring high cleanliness.
[0056] This invention utilizes SEBS, an organic framework material with ductility and elasticity, to significantly enhance the flexibility of the material, enabling it to quickly conform to complex interfaces under pressure and reduce interfacial thermal resistance. Furthermore, the synergistic effect of SEBS and DCP provides the material with excellent fatigue performance and resistance to compressive deformation, ensuring good interfacial adhesion even after repeated use. In contrast, traditional silicon-based materials lack flexibility and have poor adhesion, while the material of this invention exhibits superior interfacial adaptability, achieving a thermal resistance below 1 K·cm² / W.
[0057] This invention endows thermal interface materials with excellent heat storage properties by using paraffin wax as a phase change filler material. Paraffin wax can absorb heat within the phase change temperature range, dynamically regulating the heat distribution in the working environment, alleviating the thermal management pressure caused by the high-temperature operation of electronic devices. The introduction of phase change heat storage improves the performance of thermal management and makes the long-term operation of equipment more stable and reliable. The organic framework material and mineral thermally conductive filler of this invention can be easily separated and recycled, and have good recycling potential. Silicon-based materials may have certain environmental impacts during production and waste disposal, while the materials of this invention are composed entirely of silicon-free, non-toxic, and recyclable components, meeting environmental protection requirements. In addition, the materials of this invention do not contain harmful metals or volatile chemicals, complying with international environmental standards (such as RoHS and REACH restrictions), and can fully meet the requirements of green manufacturing.
Claims
1. A flexible, silicon-free phase change high thermal conductivity pad, characterized in that, The raw material components include: thermoplastic elastomer, crosslinking agent, phase change material, first thermally conductive filler, and second thermally conductive filler; each raw material component by mass percentage is: thermoplastic elastomer 5-30 wt%, paraffin wax 5-35 wt%, first thermally conductive filler 30-75 wt%, second thermally conductive filler 5-30 wt%, and crosslinking agent is 0.5-2 wt% of the total mass of thermoplastic elastomer and phase change material, with a total amount of 1; after the components are mixed evenly, they are hot-pressed and then calendered to shape. The thermoplastic elastomer serves as a continuous phase, providing flexibility, mechanical support, and processing performance for the entire composite material. The phase change material is used to undergo a solid-liquid phase change near the operating temperature of electronic devices to improve the material's wettability at the contact interface and reduce the interfacial contact thermal resistance. The first thermally conductive filler and the second thermally conductive filler have different microstructures.
2. The flexible silicon-free phase change high thermal conductivity pad as described in claim 1, characterized in that: The thermoplastic elastomer is one or a combination of two or more of SEBS, OBC, SBS, POE, TPU, and TPEE.
3. The flexible silicon-free phase change high thermal conductivity pad as described in claim 1, characterized in that: The phase change material is paraffin wax with a melting point of 40–80°C, which enables the material to undergo a phase change within the normal operating temperature range of electronic devices, thereby improving the interface bonding performance.
4. The flexible silicon-free phase change high thermal conductivity pad as described in claim 1, characterized in that: The first thermally conductive filler is spherical alumina particles with a particle size of 10–50 μm; the second thermally conductive filler is plate-shaped hexagonal boron nitride with an average particle size of 10–50 μm; the mass ratio of alumina to hexagonal boron nitride is 90:10–80:
20.
5. The flexible silicon-free phase change high thermal conductivity pad as described in claim 1, characterized in that: The alumina is compounded with different particle sizes to improve the packing density of the filler.
6. The flexible silicon-free phase change high thermal conductivity pad as described in claim 1, characterized in that: The crosslinking agent is 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane (DCP), and its addition amount is 0.5 to 2 wt% of the total mass of the thermoplastic elastomer and the phase change material.
7. A method for preparing a flexible, silicon-free phase change high thermal conductivity pad, characterized in that, Includes the following steps: Step 1, Material preparation: Weigh the thermoplastic elastomer, crosslinking agent, phase change material, first thermally conductive filler and second thermally conductive filler according to the set mass ratio; Step 2: Prepare thermally conductive slurry: Add the raw materials prepared in Step 1 to a planetary vacuum mixer and mix them evenly to obtain a thermally conductive slurry, so that the phase change material is uniformly coated on the surface of the thermally conductive filler. During the stirring process, the combined motion of revolution and rotation is used to uniformly disperse alumina and boron nitride in the continuous phase of thermoplastic elastomer and to uniformly coat the thermally conductive filler surface with phase change material. Step 3, hot pressing: The slurry obtained in step 2 is placed in a preheated mold for hot pressing. The hot pressing temperature is 80-180℃, the hot pressing pressure is 2-20 MPa, and the holding time is 5-60 min. Step 4: Calendering and shaping; The sheet material after hot pressing in step 3 is fed into a calendering machine for continuous calendering. The calendering temperature is 50-70℃ and the calendering ratio is 1.2-2.0, so that the sheet-like hexagonal boron nitride is oriented along the calendering direction. The calendering thickness is controlled at 0.2-5mm. After calendering, it is cooled to obtain a flexible silicon-free phase change high thermal conductivity pad.
8. The method for preparing the flexible silicon-free phase change high thermal conductivity pad as described in claim 1, characterized in that: Each raw material component should be cleaned and dried before use.